Information usefulness and usage in business decision-making: an activity-based costing (ABC) perspective - Abu Mansor, Nur Naha (Poole, Dorset, 2012)
Activity-based costing (ABC) an information system developed in the 1980s to overcome some of the limitations of traditional cost accounting and to enhance its usefulness in strategic decision-making. The objective of the study is find out how managers feel about activity-based costing, especially how useful they believe it is in providing information and in helping them to make better decisions. Data was collected by means of an e-mailed questionnaire sent out to 181 ABC users consisting of executives at a large telecommunication company in South East Asia. ABC users were asked 24 items which assessed their perceptions of the information usefulness and effects on decision making of ABC usage. Descriptive analysis on the firm's experiences with the usefulness of ABC information in different business processes and how ABC information changed decisions is presented. Respondents' were asked to indicate the significance of changes made as a result of ABC site implementation. Using this measure, when an ABC implementation causes a strong change in decisions, it is viewed as being successful; when it causes less change in decisions, it is viewed as not being successful. It also reports on the organisation's usefulness of ABC information in different business processes. By viewing an ABC system as an enabler to improve the operations business processes and decisions, it demonstrates that these systems enable executive and managers to enhance the process of decision-making. The study found ABC provided better information in areas of budgeting and planning and opportunities for improvement in other business areas. In relation to ABC making changes in business decisions, these were less successful in the various business functions. The implications of these findings share the experiences of the present organisation and their perceptions on the usefulness of ABC information and where it stands in changing business decisions in their operations.